Plato and His Legacy - Liebersohn, Yosef Z. (Cambridge Scholars Publisher, 2021)
This volume offers a detailed interpretation of Plato's texts and Platonic philosophy in its various forms and shapes as a living force in the history of philosophy, from the Hellenistic age, through the Middle Ages and Renaissance Italy, to modern England, America, Japan, and Israel. Most of the contributions here deal with the afterlife and influence of Plato's dialogues in later Greek philosophy and in various places and periods, and approach a number of dialogues and issues from new perspectives, shedding new light on some ancient problems. These studies represent no single approach, and i.